Analysis of the Recognition and Validation of Children Born Out of Wedlock and the Legal Consequences According to Civil Law and Rights Provisions - Anisa Mutiara Kartini Nasution; Nuur Zayana Purba; Nadia Agustira; Annisa Sonia Moniq Harahap; Ilham Syah (ISNU Sumatera Utara, 2025)
In this case, the law fully plays a role in enforcing proper matters, and the concept of legal marriage is an absolute necessity within the concept of marriage. While the status of a child can be considered capable and present as a balancing force, in terms of legal considerations, the existence of an illegitimate child is completely incapable of being recognized. The type of research taken is based on the focus of all results from newspapers, magazines, and articles, not only in writing, analyzing, and processing data from several data sources. This type of qualitative research has an understanding of the meaning and concept of the atmosphere of the research phenomenon developing in society. Qualitative research aims to pay attention to the meaning and concept of a phenomenon. In general, if the status of an illegitimate child is legally recognized, it is if the orphanage or social services as one of the institutions that really protects abandoned children. Because the purpose of applying the actual legal function and in the concept of legitimate and illegitimate children must be distinguished from inheritance, criminal rights, and civil rights.